Frontier Research in Behavioral Public Administration - Chen, Zhixia (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book mainly summarizes and analyzes the advanced research progress in the field of behavioral public administration, and also looks forward to the future of related academic research. It helps readers to quickly grasp the frontiers and latest developments in the field of behavioral public administration. It is benefit for readers to learn the hot topics, issues, and research methods, improving their research ability. It not only includes the frontier progress in western culture but also includes the researches in China.
Chapter 1. Introduction to the Advances of Behavioral Public Administration -- Chapter 2. Public service motivation -- Chapter 3. Psychology of public decision making -- Chapter 4. Performance management -- Chapter 5. Interaction between government and the public -- Chapter 6. Corruption -- Chapter 7. Institutional reform -- Chapter 8. Government transparency -- Chapter 9. Red tape -- Chapter 10. Citizen cooperation -- Chapter 11. Government satisfaction -- Chapter 12. Government trust.
Keywords: Psychology, Industrial; Public health; Public administration; Work and Organizational Psychology; Public Health; Public Management